Dialectic of Caning Punishment in Aceh: Contestation Between Text and Context - Faisal Yahya (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
The field study was conducted to assess how the execution of caning punishment in prison or detention center has been implemented in Aceh based on Qur'an and hadith perspective. Responding to the aim of study, an interpretation and explanation of the verses of Qur'an and hadith was done related to the implementation of the caning punishment, while the field data obtained by interview and documentation. The result of the study indicated that the execution process of caning in prison or detention center does not meet the standards in Qur'an and hadith because the procession is carried out in a closed place (prison) and access to the prison is bounded by standard rules. So the caning punishment process should be carried out in public places that are accessible to the society.Keywords: Caning Punishment; Prison or Detention Center;  Quranic, Hadith; Sharia Formal Application